Chronic Nonhealing Wounds: Could Leg Ulcers Be Hereditary?. (10th March 2013) - Nagy, Nikoletta; Szabad, Gábor; Szolnoky, Győző; Kiss-László, Zsuzsanna; Dósa-Rácz, Éva; Bata-Csörgő, Zsuzsanna; Kemény, Lajos; Széll, Márta
Abstract : Background . A number of well-known acquired and putative inherited etiological factors contribute to the development of venous leg ulcer (VLU). Aim . In this study we set out to perform a meta-analysis of putative genetic and acquired factors predisposing to VLU development. Methods . VLU patients (n = 157 ) were divided into three subgroups in accordance with their acquired etiological factors. The frequencies of four genetic factors were determined: the R506Q (Leiden) mutation of the F5 gene, the G20210A mutation of the F2 (prothrombin) gene, the 2451 A/G SNP of the fibroblast growth factor receptor 2 (FGFR2) 3′ UTR, and the −308 G/A SNP of the tumor necrosis factor α (TNFA) promoter. Results . The −308 TNFA SNP exhibited a higher frequency among VLU patients without known acquired predisposing factor in their history, than among patients with thrombosis or soft tissue infection in their history (Fisher P = 0.0173 ). Conclusions . This study has demonstrated that the group of VLU patients is heterogeneous in their genetic predisposing factors. Further large-scale studies are needed to delineate the associations among genetic and acquired etiological factors with regard to VLU development and to integrate the consequences of the already known genetic factors to the management of VLU.